Ca2+ current facilitation is CaMKII-dependent and has arrhythmogenic consequences - Bers, Donald M.; Morotti, Stefano (Frontiers in Pharmacology, 2014)
The cardiac voltage gated Ca2+ current (ICa) is critical to the electrophysiological properties, excitation-contraction coupling, mitochondrial energetics and transcriptional regulation in heart. Thus, it is not surprising that cardiac ICa is regulated by numerous pathways. This review will focus on changes in ICa that occur during the cardiac action potential (AP), with particular attention to Ca2+-dependent inactivation (CDI), Ca2+-dependent facilitation (CDF) and how calmodulin (CaM) and Ca2+-CaM dependent protein kinase (CaMKII) participate in the regulation of Ca2+ current during the cardiac AP. CDI depends on CaM pre-bound to the C-terminal of the L-type Ca2+ channel, such that Ca2+ influx and Ca2+ released from the sarcoplasmic reticulum bind to that CaM and cause CDI. In cardiac myocytes CDI normally predominates over voltage-dependent inactivation. The decrease in ICa via CDI provides direct negative feedback on the overall Ca2+ influx during a single beat, when myocyte Ca2+ loading is high. CDF builds up over several beats, depends on CaMKII-dependent Ca2+ channel phosphorylation and results in a staircase of increasing ICa peak, with progressively slower inactivation. CDF and CDI co-exist and in combination may fine-tune the ICa waveform during the cardiac AP. CDF may partially compensate for the tendency for Ca2+ channel availability to decrease at higher heart rates because of accumulating inactivation. CDF may also allow some reactivation of ICa during long duration cardiac APs, and contribute to early afterdepolarizations, a form of triggered arrhythmias.